2008
DOI: 10.3122/jabfm.2008.04.070254
|View full text |Cite
|
Sign up to set email alerts
|

High Blood Pressure Knowledge Among Primary Care Patients with Known Hypertension: A North Carolina Family Medicine Research Network (NC-FM-RN) Study

Abstract: Background: We sought to assess primary care patients' current knowledge about various aspects of high blood pressure (BP).Methods: We mailed a questionnaire to 700 hypertensive patients enrolled in a practice-based research network cohort from 24 practices in North Carolina. We determined percentages of respondents (total and by subgroups) incorrectly answering each of 6 questions pertaining to various aspects of high BP. We then examined bivariate and multivariate associations with answering 2 or more items … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
64
4
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 24 publications
8
64
4
11
Order By: Relevance
“…Over 25% of the bankers do not know whether cigarette smoking, alcohol or high salt intake is a risk factor for hypertension and at least 20% of them do not know of obesity being a risk factor while at least 25% of the traffic wardens do not know if cigarette smoking, obesity, family history or sedentary lifestyle is a risk factor for hypertension. This is also similar to a study done in North Carolina 11 in which 22% of the respondents were not aware of any preventive measures for hypertension. The implication of this is that this category of people in the population will not likely actively seek medical intervention or bother to avoid the modifiable risk factors for hypertension.…”
Section: Discussionsupporting
confidence: 75%
“…Over 25% of the bankers do not know whether cigarette smoking, alcohol or high salt intake is a risk factor for hypertension and at least 20% of them do not know of obesity being a risk factor while at least 25% of the traffic wardens do not know if cigarette smoking, obesity, family history or sedentary lifestyle is a risk factor for hypertension. This is also similar to a study done in North Carolina 11 in which 22% of the respondents were not aware of any preventive measures for hypertension. The implication of this is that this category of people in the population will not likely actively seek medical intervention or bother to avoid the modifiable risk factors for hypertension.…”
Section: Discussionsupporting
confidence: 75%
“…Similar findings have been reported, where many patients had not known the ideal blood pressure value and almost half were not aware of their own blood pressure or able to express the correct categories of high blood pressure measurements 15 . In contrast, a study done in North Carolina, USA among known hypertensive patients had revealed that only a small percentage did not know the correct value or were not sure that BP > 140/90 mmHg is hypertension 17 .…”
Section: Discussionmentioning
confidence: 93%
“…A maioria das pesquisas sobre esse tema tratam de doenças infecto-contagiosas, especialmente AIDS 4,5 . Uma questão metodológica importante é que vários estudos tratam do conhecimento que sujeitos já acometidos pelas doenças têm 6,7 . Em nosso caso, os indivíduos foram escolhidos aleatoriamente na população geral, minimizando a possibilidade de viés de seleção.…”
Section: Métodosunclassified